2008
DOI: 10.1007/s10433-008-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and quality of life of older New Zealanders with and without impaired vision: a descriptive, comparative study

Abstract: A study involving older New Zealanders (aged 65?) explored levels of life satisfaction reported by groups with and without impaired vision as well as factors contributing to and detracting from quality of life (QOL). Those with impaired vision (n = 135) had a visual acuity of 6/24 (i.e., 20/80) or worse in the better eye with corrective lenses, or a field of vision not greater than 20°at its widest diameter and had a mean age of 82.3 (SD = 6.76). Those with no significant impairment of vision (n = 425) were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…The study presented herein ties in with previous research which has found associations in later-life between poorer levels of vision and wellbeing, including depression 23 , satisfaction with life 24 , quality of life 25 and functional ability which may impact an individual's ability to be socially engaged in later life 26 . Furthermore, previous studies have also demonstrated a worsening of wellbeing with deterioration in vision 27 and an improvement after treatment of poor vision 27,28 .…”
Section: Discussionsupporting
confidence: 77%
“…The study presented herein ties in with previous research which has found associations in later-life between poorer levels of vision and wellbeing, including depression 23 , satisfaction with life 24 , quality of life 25 and functional ability which may impact an individual's ability to be socially engaged in later life 26 . Furthermore, previous studies have also demonstrated a worsening of wellbeing with deterioration in vision 27 and an improvement after treatment of poor vision 27,28 .…”
Section: Discussionsupporting
confidence: 77%
“…While one study suggested that age did not significantly affect global QOL [108], two studies suggested that age was independently associated with vision-specific QOL impairment [109] [110]. A study suggested that there was a significant interaction effect of vision status and age on life satisfaction and QOL [111].…”
Section: Agementioning
confidence: 99%
“…Many visually impaired older adults have reduced social networks due to their limited capacity to participate in social activities [28]. Social support has emerged as one of the most important contributors to HRQOL for people with visual impairments [111]. Researchers have reported that participation in social roles, social integration, and perceived support play roles in explaining the effect of visual impairment on declines in the HRQOL of older adults [31] [115].…”
Section: Social Supportmentioning
confidence: 99%
“…Older adults with age-related macular degeneration reported lower life satisfaction than adults without age-related macular degeneration (Davis, Lovie-Kitchin, & Thompson, 1995). In a comparison study of older adults with vision impairment and older adults without vision impairment in New Zealand, older adults with vision impairment endorsed lower levels of life satisfaction (η 2 = .03) (Good, 2008). There was an age interaction, such that the adults ages 65-84 with vision impairment reported significantly lower scores of life satisfaction compared to sighted older adults of the same age (η 2 = .02).…”
Section: Disability and Life Satisfactionmentioning
confidence: 98%
“…It is unknown how functional disability and vision impairment may impact reasons for living, a measure of protective factors against suicide. Both functional disability and vision impairment are related to decreased reports of life satisfaction in older adults (Borg et al, 2006;Good, 2008) Thus, both the limitations in the ability to perform activities of daily living and the presence of visual impairment are related to poor mental health functioning in older adults.…”
Section: Disability and Life Satisfactionmentioning
confidence: 99%